Global perspectives on sustainable library practices - Okojie, Victoria; Igbinovia, Magnus Osahon, 1989- (Hershey, PA : Information Science Reference, 2023)
'The aim of this book is to provide a rich and robust knowledge resource that brings together diverse sustainable library practices that will revamp library operations towards optimally meeting the current objectives of libraries as a developmental institution, as well as sustaining value for future operations and service transactions'--
Includes bibliographical references and index.
Keywords: Libraries -- Information technology; Libraries -- Information technology -- Africa; Academic libraries -- Information technology; Sustainability; Sustainable development